Gold nanorods based diffusion reflection measurements: current status and perspectives for clinical applications - Ankri Rinat; Fixler Dror (Nanophotonics, 2017)
Optical imaging is a powerful tool for investigating the structure and function of tissues. Tissue optical imaging technologies are generally discussed under two broad regimes: microscopic and macroscopic, while the latter is widely investigated in the field of light-tissue interaction. Among the developed optical technologies for tissue investigation, the diffusion reflectance (DR) method is a simple and safe technology. However, this method suffers from low specificity and low signal-to-noise ratio, so the extraction of the tissue properties is not an easy task. In this review, we describe the use of gold nanorods (GNRs) in DR spectroscopy. The GNRs present unique optical properties which enhance the scattering and absorption properties of a tissue. The GNRs can be easily targeted toward abnormal sites in order to improve the DR signal and to distinguish between the healthy and the abnormal sites in the tissue, with high specificity. This article describes the use of the DR-GNRs method for the detection of cancer and atherosclerosis, from light transfer theory, through the extraction of the tissue properties using the diffusion theory and up to DR in vivo measurements.